Characterization of mannanase S1 from Klebsiella oxytoca KUB-CW2-3 and its application in copra mannan hydrolysis - Titapoka Chantorn, Sudathip; Pongsapipatana, Nawapan; Keawsompong, Suttipan; Ingkakul, Arunee; Haltrich, Dietmar; Nitisinprasert, Sunee (ScienceAsia : journal of the Science Society of Thailand, 2013)
Abstract only